Спосіб дослідження параметрів дорожнього руху - Паснак, Іван (Посвіт, 2019)
The paper proved the feasibility of drones to study options for transport and pedestrian flows. Traffic analysis method was developed and patented.
Method for investigation the road traffic parameters
Keywords: 656.1